Edukasi Gizi Isi Piringku Anak Sekolah SD 07 Kramat Pela Jakarta Selatan - Rosmida M. Marbun; Meilinasari; Anastu Regita Nareswara; Ratih Puspitaningtyas Purbaningrum; Ani Noviani (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The problem of nutritional imbalance in school-aged children remains a serious concern in Indonesia. Based on the 2023 Indonesian Health Survey (SKI), only 6.6% of children aged 5–12 years consumed the recommended amount of fruits and vegetables. Education about balanced nutrition through visual approaches such as "Isi Piringku" (My Plate) is important from an early age to improve nutritional literacy. This community service activity aims to improve students' understanding of the concept of a healthy plate at SDN 07 Kramat Pela, South Jakarta. The majority of students (56.2%) were female. In terms of nutritional status, the majority (53.3%) were underweight. Therefore, nutrition education is crucial for improving knowledge and is expected to be applied in daily life. The methods used included lectures, interactive discussions, demontration, visual media (posters, leaflets, food models), and educational games. Evaluation was carried out through pre- and post-tests. The results showed an increase in knowledge, with the "good" category increasing from 46.8% to 74.2%, and the median score increasing from 70 to 80. Education based on visual and participatory approaches has proven effective in improving children's understanding of balanced nutrition. This intervention is recommended for continuous implementation in elementary schools to foster long-term healthy eating habits.